Structural Modeling on the Determinants of Effectiveness of SOPs Containing COVID-19 in Mass Gatherings - Basit, Abdul; Scholz, Miklas; Niazi, Abdul Aziz Khan; Qazi, Tehmina Fiaz; Shaukat, Muhammad Zeeshan; Rao, Zia-ur-Rehman; Mahmood, Asif (Frontiers in Psychology, 2021)
The study is aimed to analyze the determinants of effectiveness of SOPs in mass gatherings for containing COVID-19. Overall design of the study embraces literature review, data collection by field survey, structural modeling and analysis. The study is built on the experts’ opinion of a focus group representing the people recently participated and responsible for mass gathering. The study uses discourse of literature review for identification of the determinants, Interpretive Structural Modeling (ISM) for developing & analyzing structural model and Matriced' Impacts Croise's Multiplication Appliquée a UN Classement (MICMAC) for corroboration of results of ISM/classification of determinants. As a result of review of literature, a list of determinants is generated and verified from panel of experts. Results of ISM revealed that the determinants namely ‘legal environment of the country’, ‘practicability of SOPs’, ‘perceived benefit of adapting SOPs’ and ‘possibilities of avoiding gathering’ occupy top of the model, therefore, they are less critical determinants, whereas, ‘nature of gathering’ occupy bottom of the model, hence it is the most critical determinant. Remaining form middle of the model and therefore, they are moderate severe. Results of MICMAC show that determinant ‘perceived benefit of adapting SOPs’ is dependent, ‘nature of gathering’ is independent and all others are linking. The results of MICMAC implicitly substantiate the findings of ISM. Overall results of the study show that ‘nature of gathering’ is the key determinant. The study does not require priori theory since it is a theory building research that uses inductive approach. It is based on real data and it is useful for local authorities, organizers, participants (attendees/visitors) of mass gatherings, health officials/regulators, researchers and community at large. This study has fundamental importance for planning and preparing for such events while ensuring minimum risk of COVID-19 transmission.